Aktor dan Media Dalam Komunikasi Politik - Marzuki Marzuki; Nayla Putri Kamila; Lolo Ate Karina Berutu (Lembaga Pengembangan Kinerja Dosen, 2025)
The political transformation in post-New Order Indonesia has opened up space for public participation and press freedom in democratic life. In this context, mass media and social media play an important role in shaping people's political awareness. They also influence political behavior. This research aims to analyze the contribution of print and digital media in delivering political messages. The media also plays a role in building public opinion and shaping the political image of certain actors. This research examines various political communication literature and theories as well as the involvement of actors such as politicians, media professionals, and activists with a qualitative method through a literature study approach. The research proves that the media has the ability to shape socio-political reality through agenda-setting mechanisms in addition to being a means of disseminating information. Social media is now an effective campaign tool as well, with a significant influence on people's political attitudes, depending on the credibility of the political communicator, the background of the audience, and the quality of the message. That the media is a strategic instrument in modern political communication and helps determine the direction of democratic dynamics in Indonesia has been confirmed by these findings.